2020
DOI: 10.1038/s41598-020-70812-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide analysis of SARS-CoV-2 virus strains circulating worldwide implicates heterogeneity

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a novel evolutionary divergent RNA virus, is responsible for the present devastating COVID-19 pandemic. To explore the genomic signatures, we comprehensively analyzed 2,492 complete and/or near-complete genome sequences of SARS-CoV-2 strains reported from across the globe to the GISAID database up to 30 March 2020. Genome-wide annotations revealed 1,516 nucleotide-level variations at different positions throughout the entire genome of SARS-CoV-2. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
289
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(319 citation statements)
references
References 40 publications
19
289
1
1
Order By: Relevance
“…To this regard, we note that the two common endemic human coronaviruses, HCoV-OC43 [33] and HCoV-299E [34], have extensive deletions in the C-terminal region of nsp1. Thought crystallization and biological data are needed to confirm our hypothesis, our observations, together with the recent findings of two viral strains carrying in one case an extensive deletion in the orf7a gene [35], a deletion in the nsp2 gene [36] and deletions in nsp1 gene also identified by other groups [37,38], indicate that SARS-CoV-2 genome may be undergoing a significant evolutionary process, which may result in virushost adaptation [39]. Since the overwhelming majority of genomic sequences collected so far are from symptomatic subjects, it seems logical to characterize in detail SARS-CoV-2 genomes from the asymptomatic population.…”
Section: Discussionsupporting
confidence: 82%
“…To this regard, we note that the two common endemic human coronaviruses, HCoV-OC43 [33] and HCoV-299E [34], have extensive deletions in the C-terminal region of nsp1. Thought crystallization and biological data are needed to confirm our hypothesis, our observations, together with the recent findings of two viral strains carrying in one case an extensive deletion in the orf7a gene [35], a deletion in the nsp2 gene [36] and deletions in nsp1 gene also identified by other groups [37,38], indicate that SARS-CoV-2 genome may be undergoing a significant evolutionary process, which may result in virushost adaptation [39]. Since the overwhelming majority of genomic sequences collected so far are from symptomatic subjects, it seems logical to characterize in detail SARS-CoV-2 genomes from the asymptomatic population.…”
Section: Discussionsupporting
confidence: 82%
“…Approximately, 30 kilobase sized genome of the novel SARS-CoV-2 encodes several smaller open reading frames (ORFs) (Rota et al, 2003;Freundt et al, 2010, Cotten et al, 2013. These ORFs encode for different proteins for example the replicase polyprotein, the spike (S) glycoprotein, envelope (E), membrane (M), nucleocapsid (N) proteins, accessory proteins, and other non-structural proteins (nsp) (Ahmed, Quadeer & McKay, 2020;Islam et al, 2020;Phan, 2020;Walls et al, 2020). The genome of SARS-CoV-2 coupled with regions of genomic instability (Abdelmageed et al, 2020;Rahman et al, 2020), which encodes for multiple structural and non-structural proteins (Ahmed, Quadeer & McKay, 2020;Rahman et al, 2020) with many unique features.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of SARS-CoV-2 coupled with regions of genomic instability (Abdelmageed et al, 2020;Rahman et al, 2020), which encodes for multiple structural and non-structural proteins (Ahmed, Quadeer & McKay, 2020;Rahman et al, 2020) with many unique features. These features make these proteins prone to frequent coding changes, thus generating new strains in a short period of time (Hemida & Abduallah, 2020;Islam et al, 2020). Rapid mutational frequencies are associated with the poor proofreading efficiency of the viral RNA polymerase, and the likelihood of recombination between different members of this family (Jackwood, Hall & Handel, 2012;Phan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may contribute to understand the pathogenic dynamics of the virus over time. The genetic differences among SARS-CoV-2 strains from different location can be linked with their geographical distributions (12). The recent studies suggested that dry and cold climate can boost the spreading of the infections (13).…”
Section: Introductionmentioning
confidence: 99%